Getting to Know Values and Character Education in Pantun: Stylistic Studies - Riskida Pitamaro Tambunan; Rosmawaty Rosmawaty (Journal of Aceh Studies, 2026)
The aim of education in Indonesia from time to time has always included the formation of character or moral values in students. Pantun, as an old form of poetry, is a vehicle for conveying values and deep character education. This stylistic study aims to identify and analyze the values and character education contained in pantun. Through a text analysis approach, values such as morals, values. With the many learning materials, it turns out that learning rhymes has enormous potential in building good character or values, with the moral values or messages contained in rhymes. This article uses the research method library research, and internet searching to help obtain information for each discussion, as well as collecting data or articles from the internet, especially from official websites and various other sources to find out more about studying pantun stylistically.